# arrow_back SImplify $\dfrac{1+\cot ^{2} \theta}{\sec ^{2} \theta}$

98 views
SImplify $\dfrac{1+\cot ^{2} \theta}{\sec ^{2} \theta}$

$\dfrac{\csc ^{2} \theta}{\sec ^{2} \theta}=\frac{\dfrac{1}{\sin ^{2} \theta}}{\frac{1}{\cos ^{2} \theta}}=\dfrac{\cos ^{2} \theta}{\sin ^{2} \theta}=\cot ^{2} x$
by Bronze Status
(7,476 points)

## Related questions

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve $\lim _{x \rightarrow \pi / 4} \dfrac{\sqrt{2} \cos x-1}{\cot x-1}$
Solve $\lim _{x \rightarrow \pi / 4} \dfrac{\sqrt{2} \cos x-1}{\cot x-1}$Solve $\lim _{x \rightarrow \pi / 4} \dfrac{\sqrt{2} \cos x-1}{\cot x-1}$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
$\lim _{x \rightarrow \pi / 2}(\sec \theta-\tan \theta)=$
$\lim _{x \rightarrow \pi / 2}(\sec \theta-\tan \theta)=$$\lim _{x \rightarrow \pi / 2}(\sec \theta-\tan \theta)=$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Simplify $\left(\dfrac{2 x^{3}}{8 y^{-4}}\right)^{-3}$
Simplify $\left(\dfrac{2 x^{3}}{8 y^{-4}}\right)^{-3}$Simplify $\left(\dfrac{2 x^{3}}{8 y^{-4}}\right)^{-3}$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
How do you solve $\dfrac{1}{2\sqrt{2x-5}-1}{2\sqrt{3x+4}}=-1$?
How do you solve $\dfrac{1}{2\sqrt{2x-5}-1}{2\sqrt{3x+4}}=-1$?How do you solve $\dfrac{1}{2\sqrt{2x-5 }-1}\cdot{2\sqrt{3x+4}}=-1$? ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Determine $\lim_{x \rightarrow \frac{1}{2}}\dfrac{2x}{x+\frac{1}{x}}$
Determine $\lim_{x \rightarrow \frac{1}{2}}\dfrac{2x}{x+\frac{1}{x}}$Determine $\lim_{x \rightarrow \frac{1}{2}}\dfrac{2x}{x+\frac{1}{x}}$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Evaluate $\lim_{x \rightarrow -\infty}\dfrac{1}{2x^3}$
Evaluate $\lim_{x \rightarrow -\infty}\dfrac{1}{2x^3}$Evaluate $\lim_{x \rightarrow -\infty}\dfrac{1}{2x^3}$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Evaluate the limit $\lim_{x\rightarrow 0}{(e^x+3x)}^{\dfrac{1}{x}}$?
Evaluate the limit $\lim_{x\rightarrow 0}{(e^x+3x)}^{\dfrac{1}{x}}$?Evaluate the limit $\lim_{x\rightarrow 0}{(e^x+3x)}^{\dfrac{1}{x}}$? ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
How do you evaluate $\lim_{x \rightarrow 0} {\dfrac{\sqrt{4+x} - 2} {3x}}$
How do you evaluate $\lim_{x \rightarrow 0} {\dfrac{\sqrt{4+x} - 2} {3x}}$How do you evaluate $\lim_{x \rightarrow 0} {\dfrac{\sqrt{4+x} - 2} {3x}}$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Determine $\lim_{x \rightarrow 9}\dfrac{x^2-81}{\sqrt{x}-3}$
Determine $\lim_{x \rightarrow 9}\dfrac{x^2-81}{\sqrt{x}-3}$Determine $\lim_{x \rightarrow 9}\dfrac{x^2-81}{\sqrt{x}-3}$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Determine $\lim_{x \rightarrow \infty}\dfrac{4x^3+x^2}{x^3+3}$
Determine $\lim_{x \rightarrow \infty}\dfrac{4x^3+x^2}{x^3+3}$Determine $\lim_{x \rightarrow \infty}\dfrac{4x^3+x^2}{x^3+3}$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Simplify: $\left(4 x^{2}-2 x\right)-\left(-5 x^{2}-8 x\right)$
Simplify: $\left(4 x^{2}-2 x\right)-\left(-5 x^{2}-8 x\right)$Simplify: $\left(4 x^{2}-2 x\right)-\left(-5 x^{2}-8 x\right)$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
If $\mathrm{f}(9)=9, \mathrm{f}^{\prime}(9)=4$, then $\lim _{x \rightarrow 9} \dfrac{\sqrt{f(x)}-3}{\sqrt{x}-3}$
If $\mathrm{f}(9)=9, \mathrm{f}^{\prime}(9)=4$, then $\lim _{x \rightarrow 9} \dfrac{\sqrt{f(x)}-3}{\sqrt{x}-3}$If $\mathrm{f}(9)=9, \mathrm{f}^{\prime}(9)=4$, then $\lim _{x \rightarrow 9} \dfrac{\sqrt{f(x)}-3}{\sqrt{x}-3}$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Find the limit $\lim _{x \rightarrow \infty} \frac{3 x+1}{|x|+2}$
Find the limit $\lim _{x \rightarrow \infty} \frac{3 x+1}{|x|+2}$Find the limit $\lim _{x \rightarrow \infty} \dfrac{3 x+1}{|x|+2}$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Find the limit $\lim _{x \rightarrow \infty} \frac{6 x^{2}-4 x^{5}+7 x-1}{12 x^{5}-3 x^{2}+2}$
Find the limit $\lim _{x \rightarrow \infty} \frac{6 x^{2}-4 x^{5}+7 x-1}{12 x^{5}-3 x^{2}+2}$Find the limit $\lim _{x \rightarrow \infty} \dfrac{6 x^{2}-4 x^{5}+7 x-1}{12 x^{5}-3 x^{2}+2}$ ...
Find the limit $\lim _{x \rightarrow \infty} \frac{x^{3}-6 x+1}{x^{2}+2 x-3}$
Find the limit $\lim _{x \rightarrow \infty} \frac{x^{3}-6 x+1}{x^{2}+2 x-3}$Find the limit $\lim _{x \rightarrow \infty} \dfrac{x^{3}-6 x+1}{x^{2}+2 x-3}$ ...